2014
DOI: 10.1016/j.dsr.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Asphalt mounds and associated biota on the Angolan margin

Abstract: Keywords: 6145 0 S 11100 0 E Deep-sea benthic biology Megafauna Hydrocarbon seep Chemosynthetic environment Remotely operated vehicle Seafloor geology Habitat heterogeneity a b s t r a c t Release of hydrocarbons from sediments is important in increasing habitat heterogeneity on deep ocean margins. Heterogeneity arises from variation in abiotic and biotic conditions, including changes in substratum, geochemistry, fluid flow, biological communities and ecological interactions. The seepage of heavy hydrocarbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 58 publications
1
37
0
1
Order By: Relevance
“…The discovery of asphalt seeps in North São Paulo Plateau was an important milestone in studies of hydrocarbon seep environments and their associated chemosynthetic communities. This asphalt seep is similar to asphalt systems found in Campeche Knolls of southern Gulf of Mexico [28] and Angola Margin [29]. However, Fujikura et al (2017) analyzed the oil from the asphalt seep and their results indicated that this system was not capable of sustaining chemosynthetic communities.…”
Section: Discussionmentioning
confidence: 61%
“…The discovery of asphalt seeps in North São Paulo Plateau was an important milestone in studies of hydrocarbon seep environments and their associated chemosynthetic communities. This asphalt seep is similar to asphalt systems found in Campeche Knolls of southern Gulf of Mexico [28] and Angola Margin [29]. However, Fujikura et al (2017) analyzed the oil from the asphalt seep and their results indicated that this system was not capable of sustaining chemosynthetic communities.…”
Section: Discussionmentioning
confidence: 61%
“…Methane seeps frequently occur in areas of economic interest because of their direct association with oil and gas-rich fluids (Sibuet and Olu, 1998;Bergquist et al, 2003;Cordes et al, 2003Cordes et al, , 2016Bernardino et al, 2012;Jones et al, 2014). Although there has been wide-ranging deep-sea exploration off Trinidad and Tobago, the majority of this work has been undertaken by oil and natural gas companies and the data have not been made publically available.…”
Section: Stewardship Of the Deep Ocean Of Trinidad And Tobagomentioning
confidence: 99%
“…Natural seepage of fluids at the sea‐floor ranges from kilometre‐scale eruptive mud volcanoes with associated caldera collapses (Gray, Dingler and Wood ) to decametre‐scale extrusion of asphalt at the seafloor formation, pockmarks, and authigenic bacteria‐mediated carbonate crusts (Hovland, Gardner and Judd ; Jones et al . ). Fluid expulsion can create corrosive pore fluids and local modification of seafloor geotechnical properties (Thomas et al .…”
Section: Marine Geohazards and Conventional Assessment Techniquesmentioning
confidence: 99%